Analisis Kebutuhan Siswa Dalam Pembelajaran Daring Di Sekolah Dasar Negeri 2 Paseh - Listya Anggraeni; Khusnul Fajriyah; Sunan Baedowi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The research context that drives this research is the implementation of online learning due to the Covid-19 pandemic. The purpose of this research is to find out the needs of students in online learning at SD Negeri 2 Paseh. The method in this research is descriptive qualitative research. Sources of data in this study were students, teachers, and parents/guardians of grade III, IV, V SD Negeri 2 Paseh. The data in this study were obtained from questionnaires, interviews, and documentation. Based on the research findings of the analysis and discussion that have been described, the researchers obtained the results of the overall analysis that students have physiological needs and learning needs in online learning. Physiological needs are in the form of clothing needs, food needs, and board needs. While learning needs are in the form of needs related to learning, related to work assignments, related to services, equality of access to quality education. However, from the results of research in meeting these needs, it is still not optimal but overall it has been fulfilled.